How can educational policy support the application of the Rasch Model for character E-assessment in elementary schools during Indonesia's new normal era? - Iva Sarifah; Nina Nurhasanah; Uswatun Hasanah; Arita Marini; Uyu Muawanah (Social Sciences and Humanities Open, 2025)
The development of character education among elementary school-age children warrants significant attention, as this stage serves as the foundational period for cultivating character. This study focuses on creating an assessment instrument for character that aligns with the profile of Pancasila students. The research involved 575 respondents from grades IV, V, and VI in the DKI Jakarta area. Through a survey method, the study aimed to gauge the character values of these students. The findings indicate that the majority of the character development among the respondents falls within the moderate range. This suggests that there is a critical need for ongoing efforts to embed character education within both curricular and non-curricular activities. To analyze the data effectively, the Rasch Model was employed, demonstrating its capability to evaluate students' character through polytomous data and parametric statistical testing. The Rasch Model proves to be a relevant and effective tool for establishing the relationship between an individual's abilities and the corresponding item difficulty levels. This approach not only enhances the understanding of character development in students but also provides valuable insights for educators and policymakers seeking to improve character education initiatives in Indonesia. By aligning educational practices with the Pancasila student profile, this study contributes to the broader goal of fostering well-rounded, morally grounded individuals in society.